2006
DOI: 10.1007/bf03349209
|View full text |Cite
|
Sign up to set email alerts
|

Islet cell, thyroid, adrenal and celiac disease related autoantibodies in patients with Type 1 diabetes from Sri Lanka

Abstract: Diabetes associated autoantibodies were detected in the majority of Type 1 DM subjects, suggesting a major role for autoimmunity in the pathogenesis of Type 1 DM in Sri Lankans. The prevalence of TgAb and TPOAb in Type 1 DM subjects and non-diabetic controls was relatively high and similar in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
1
8
1
Order By: Relevance
“…In the present study, the rate of positive anti-TPO and/or anti-TG was 20.2% and 10.3% in the patient and control groups, respectively. In the study by Premawardhana et al, patient and control groups had an anti-TG positivity of 25% and 33%, respectively, and for anti-TPO, these rates were as 22% and 18%, respectively; there was no statistical difference between these groups [22]. Previous studies have reported that TA is more frequent among girls than boys [21,23], while the present authors and others [19,24] have not found such a difference.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…In the present study, the rate of positive anti-TPO and/or anti-TG was 20.2% and 10.3% in the patient and control groups, respectively. In the study by Premawardhana et al, patient and control groups had an anti-TG positivity of 25% and 33%, respectively, and for anti-TPO, these rates were as 22% and 18%, respectively; there was no statistical difference between these groups [22]. Previous studies have reported that TA is more frequent among girls than boys [21,23], while the present authors and others [19,24] have not found such a difference.…”
Section: Discussioncontrasting
confidence: 45%
“…This difference was not statistically significant when compared with the 22% positivity among cases negative for anti-GAD [10]. Premawardhana et al did not find any statistical difference between anti-GAD65/anti-IA-2 positive and negative type 1 DM patients in terms of TA [22]. This may reflect ethnic differences, difference in iodine intake, or genetic heterogeneity in the role of TA and anti-GAD autoimmunity in type 1 DM with thyroid autoimmunity.…”
Section: Discussionmentioning
confidence: 88%
“…These TgAbs were not associated with thyroid dysfunction and probably represented a non-pathological antibody response to iodination (6). Recently, we also reported a high frequency of TgAbs in Sri Lankan patients with T1DM (7). The clinical significance of TgAbs in these diabetic patients is thus unclear and a point of interest is whether they indicate thyroiditis or whether they simply represent a non-pathological effect of iodination.…”
Section: Introductionmentioning
confidence: 74%
“…Details of the prevalence of other disease-associated antibodies in the group have been described elsewhere (7). T1DM was diagnosed according to WHO criteria (13).…”
Section: Subjectsmentioning
confidence: 99%
“…(a) diagnosing T1D - there are only sparse data about T1D related autoantibody prevalence either at diagnosis or thereafter in Sri Lankan children ( 9 ). Sensitive assays for T1D related autoantibodies identify variable percentages of antibody positive subjects at diagnosis and in established T1D, associated with regional variability, as described in a recent review ( 10 ).…”
Section: Introductionmentioning
confidence: 99%